2003
DOI: 10.1111/j.1348-0421.2003.tb03470.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus (HCMV) IE1 Plays Role in Resistance to Apoptosis with Etoposide in Cancer Cell Line by Cdk2 Accumulation

Abstract: Human cytomegalovirus (HCMV) has many strategies to survive the attack of the host. HCMV infection of host cells induces cellular activation and disturbance of the cell cycle. It is possible that HCMV modulates the behavior of certain cancer cells that are susceptible to HCMV infection. This study was performed to identify the possible mechanism of resistance to apoptotic stimuli in some cancer cell lines by HCMV infection. HCMV‐infected cancer cells showed resistance to apoptosis induced by the topoisomerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…IEKD induced apoptotic cell death specifically in HCMV infected GSC (Figure 4D). Taken together, these results reveal an important anti-apoptotic role for IE1 in HCMV infected GSC, as it has been reported in other cell systems (32–34). …”
Section: Resultssupporting
confidence: 89%
“…IEKD induced apoptotic cell death specifically in HCMV infected GSC (Figure 4D). Taken together, these results reveal an important anti-apoptotic role for IE1 in HCMV infected GSC, as it has been reported in other cell systems (32–34). …”
Section: Resultssupporting
confidence: 89%
“…Many data have indicated that both IE1 and IE2 stimulate transcription from a variety of cellular and viral genes involved in viral replication and cell survival, alone or in concert with other transcriptional regulators, including the Rb family members, the E2F family members, p53, SP1, TAFII130/TAF4 and histone modification proteins (Bonin & McDougall, 1997;Bryant et al, 2000;Fortunato et al, 1997;Hayhurst et al, 1995;Lukac et al, 1997;Margolis et al, 1995;Nevels et al, 2004b;Pajovic et al, 1997;Poma et al, 1996;Schwartz et al, 1996). The interplay between the IE proteins of HCMV and cellular factors has been implicated in disrupting normal cell-cycle progression and impeding apoptosis (Castillo et al, 2000;Kim et al, 2003;Lukac & Alwine, 1999;Murphy et al, 2000;Song & Stinski, 2002;Tanaka et al, 1999;Yu & Alwine, 2002;Zhu et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…We utilized cell line UMG1-2 that constitutively expresses HCMV IE1 protein in U373MG cells (ATCC HTB 17) (15). U373MG cells transfected with the empty retrovirus vector LNCX2 vector (Clontech, Palo Alto, CA, U.S.A.) was used as the control.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, we focused on the HCMV gene products from the major immediate early (IE) gene. By utilizing a U373MG cell line expressing HCMV IE1 protein (15), we investigated the function of HCMV IE1 protein in modulating HSV-1 induced syncytial formation.…”
Section: Introductionmentioning
confidence: 99%